Desenvolvimento de novos derivados indólicos e benzimidazólicos como potenciais sondas fluorescentes - Monteiro, Kadja Luana Chagas (2021)
Small organic molecules with fluorescent properties when in contact with an analyte have become a topic of intense research in recent years. Labeled as fluorescent probes, these act as cellular beacons and have several fluorescence mechanisms. The benzimidazole and indole derivatives are examples of important fluorophores found in several dyes and organic probes, in addition to having a recognized affinity for several biomolecules, such as DNA and serum albumin; for this reason, they were selected for the synthesis of the probes proposed in this work. The synthesis strategy consists in the condensation of the mentioned heterocycles with p-functionalized aldehydes by aromatic amines, aliphatic amines and boronic acids through the formation of an azomethine bond, promoting the extension of electron displacement, essential for fluorescence. The reaction intermediates were synthesized through Buchwald-Hartwig, Suzuki-Miyaura and SNAr reactions, where eight benzaldehydes were obtained. Yields ranged from 23-84% for indole derivatives and 10-37% for benzimidazole derivatives. The compounds were evaluated for purity by chromatography, as well as by determining the melting range. Structural characterization was performed by 1H and 13C NMR. Through a preliminary analysis, four of the thirteen synthesized probes showed a significant fluorescence response in contact with BSA. Of these, the KCH60 probe (λex / λem = 415/555 nm) was selected for tests to optimize analytical parameters. The Britton-Robinson buffer at 10 mM (pH 6) and the probe concentration at 5 μM showed maximum sensitivity. The stoichiometry of the probe-BSA complex was 1:1 (Job method). The linear range was 0.5 - 4.0 μM with a detection limit of 0.38 μM and RSD <6.0% for BSA. Finally, it is expected that these results will enable the use of these derivatives in assays for the quantification of serum albumin in real samples, in addition to enabling the design of new active molecules and/or with fluorescent properties.